Research on multilevel evaluations and zones of territorial spatial functions in Yibin, China - Meng, Bao; Zhang, Shaoyao; Deng, Wei; Peng, Li (Frontiers in Environmental Science, 2023)
Objectively evaluating and defining territorial spatial functions are important prerequisites for optimizing the use of territorial space. However, the results of the evaluation of functions at different levels may differ significantly. How to integrate the evaluation results and guide the spatial utilization at different levels more effectively is worth exploring. In this study, 185 towns in Yinbin were taken as the primary evaluation units for an indicator system of territorial spatial function constructed on the basis of multivariate data. Research methods such as the entropy method and cluster analysis were adopted to do multilevel evaluations and zoning of territorial spatial functions in Yibin City. The results suggest the following: (1) The distribution of agricultural production, rural living, and eco-logical regulation functions among the second-level production-living-ecological (PLE) functions of townships were relatively bal-anced in Yibin City. The production function of industry and mining, urban life function, and ecological product supply function showed spatial directivity. (2) The evaluation results of the first-level PLE functions of townships showed that the areas with substantial PLE functions accounted for approximately 20%, whereas the areas with insignificant functions accounted for approximately 80%, which reflected the “80/20 rule” of spatial functions. (3) In accordance with the cluster analysis of the multilevel evaluation results, the township functions in Yibin were divided into 5 functional areas: urban life-industrial production advantage areas (12%), urban life-rural life advantage areas (8%), rural life-agricultural production-ecological function product supply advantage areas (29%), rural life-agricultural production-ecological service function advantage areas (20%), and ecological service function-agricultural production function advantage areas (31%).(4) In the future, Yibin City should focus on 20 % of the significant functional areas and attach importance to the relativity of spatial functions to form a high-quality territorial spatial protection and development pattern. Based on the objectives and requirements of the new territorial spatial planning in China, this study reconstructed the municipal territorial spatial functional areas through a multilevel functional evaluation, which has theoretical and practical significance for forming a new pattern of territorial spatial development and use with joint production, living, and ecological functions.